Ballast Water Treatment (WBT) Technology dan Implementasi Konvensi Internasional untuk Kapal Berbendera Indonesia - P, Budi; Kurniawan, Ratna Dwi; JS, Nanang (Marine Science and Technology Journal; Vol 1 No 1 (2020): Marine Science and Technology Journal, 2020)
The invasion of new species, even new diseases, in an environment can threat existing species and environmental balance. As the COVID 19 pandemic, that the virus spreads so fast, through physical contact. As to the spread of COVID 19, the movement of marine biota that enters and exits along with ballast water used by ships has long been regulated in a convention of IMO. In the regulation it is clear that the deadline for ships to have ballast water treatment is September 2017, but after 3 years have passed, have these rules been implemented in Indonesia? From the results of the interviews of several domestic broadcasting companies there are have already run the convention and have not completely equipped their vessels with WBT. In this article we will discuss theregulation / policy basis of the government, and the technologies that can be applied and meet the standards.